Front Cover Image, Volume 118, Number 3, March 2021. Issue 3 (18th February 2021) - Alkayyali, Tartela; Pope, Emily; Wheatley, Sydney K.; Cartmell, Christopher; Haltli, Bradley; Kerr, Russell G.; Ahmadi, Ali
Abstract : The cover image is based on the Article Development of a microbe domestication pod (MD Pod) for in situ cultivation of micro‐encapsulated marine bacteria by Tartela Alkayyali et al., https://doi.org/10.1002/bit.27633 .